1998
DOI: 10.1038/sj.jhh.1000540
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) in hypertensive patients

Abstract: However, higher plasma concentrations of Lp(a), albeit within the normal range, could be an independent risk women) were studied and compared with 89 controls (36 men and 53 women) matched in terms of age, sex, body factor for atherosclerosis, and could contribute towards increasing the incidence of cardiovascular disease in mass index (BMI) and smoking habits. It was found that the hypertensive patients had higher plasma concenpeople with essential arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
2
15
0
1
Order By: Relevance
“…32 In addition, several studies have found a correlation between the prevalence of hypertension in blacks and both higher levels of lipoprotein(a) and greater thickness of the left ventricular septal and posterior walls. 33,34 It has also been shown that African Americans respond less favorably to certain antihypertensive drug therapies, particularly ␤-blockers and ACE inhibitors. 35 Sociocultural, economic, and environmental determinants may also influence the potency of certain risk factors such as hypertension in blacks and Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, several studies have found a correlation between the prevalence of hypertension in blacks and both higher levels of lipoprotein(a) and greater thickness of the left ventricular septal and posterior walls. 33,34 It has also been shown that African Americans respond less favorably to certain antihypertensive drug therapies, particularly ␤-blockers and ACE inhibitors. 35 Sociocultural, economic, and environmental determinants may also influence the potency of certain risk factors such as hypertension in blacks and Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found that the hypertensive patients had higher plasma concentrations of Lp (a) than in the controls. In a similar study, Catalano et al 8 reported significantly elevated levels of plasma Lp(a) in 123 Caucasian essential arterial hypertensive patients (47 men and 76 women). The pathogenicity and atherogenic role of Lp (a) is greatly influenced by the concentration of other serum lipids and lipoproteins.…”
Section: Discussionmentioning
confidence: 79%
“…Our present study demonstrated no significant differences in the conventional lipid profile, but that may be because lipid lowering drugs are commonly prescribed medication for hypertensive patients in Thailand. Some patients may have had clinically silent vascular disease resulting from increased Lp(a), hs-CRP levels and oxidative stress, rather than by hypertension [17]. Thus, the increased concentrations of Lp(a), hs-CRP and decreased eGFR in the hypertensive patients could constitute a first pathological sign, in the absence of organ damages.…”
Section: Discussionmentioning
confidence: 99%